Analisis kegagalan dengan menggunakan metode FMEA dan FTA untuk menentukan perawatan undercarriage pada kendaraan listrik e-niaga geni biru tiga roda - Hendratmoko, Tony (Journal of New Energies and Manufacturing, 2022)
Electric motorcycles are a growing transportation among the people. There are components that are slightly different from the combustion motor in general. With a variety of components, of course, there is a potential for failure both in the production process and from the part components themselves. This study aims to find out and determine what critical components are in the 3-Wheel Geni Biru E-Commerce vehicle, as well as as part of continuous innovation, control against production defects or product failures. Control of production defects or product failures can also increase consumer confidence in the products being sold. By taking a gradual approach starting from identification, data collection of damage, then using the Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) method, combined with direct testing of vehicles with overload to analyze the dominant causes. In the next stage of the dominant cause that has been obtained, a risk probability calculation (RPN) will be carried out, so that it can be further analyzed with the pareto method to reduce the majority percentage to establish an effective improvement plan. From the analysis obtained, it turns out that the bearing is a critical component of this vehicle with a value of RPN 18. Then using manual calculations they searched for the life ability of the bearing. The result is that the back wheel bearings can last for approximately 15 months with a total load of 750 kg. Thus it can be determined which components are critical components and become maintenance priorities on the 3-Wheel Geni Biru E-Commerce electric vehicle.